Cerebral Abscess in Adult with Atrial Septal Defect and Pulmonary Stenosis - Putra GB., et al (ACI (Acta Cardiologia Indonesiana), 2017)
Cerebral Abscess in Adult with Atrial Septal Defect and Pulmonary Stenosis